The Long-Term Impact of Christian Missionaries on Human Capital: Evidence from Nigeria - Olajutemu, Olatunbosun Kunle (Université d'Ottawa | University of Ottawa, 2013)
This study examines the long-term impact of exposure to missionary activities on education attainment in Nigeria. Using information on the locations of Christian missions, I find that generally, there is a strong positive effect of historical exposure to missionary activities on education attainment today in Nigeria. However, the impact varies across tribal and religious groups. The impact is stronger today among northern tribes and the Muslims than the southern tribes and the Christians. The reason being that, education in the south and among the Christians is approaching its peak while education in the north and among the Muslims started developing in recent years. Therefore, any increase in the number of mission stations will have a small impact on education development in the south unlike the north. More so, historically; the Southerners were first exposed to Christian missionary activities and were early school starters unlike the north that opposed education as an agent of Christianity and only saw the need for western education recently. I also find that exposure to Christian missionary activities reduces the gender gap in education attainment, even eliminating it in certain tribes.